Metonymy according to Abdul Qaher Al-Jurjani in his book Dala’il Al-I’jaz - Alsaedi, Manal (Al-Adab Journal, 2023)
The manuscript aims to study the term metonymy used by Abd al-Qaher al-Jurjani in his book "Dalail al-I’jaz", and to know its role in the rooting of this science and the relationship between metonymy as an art and its meaning. The manuscript is organized into three sections, an introduction, two main points, and conclusion. The introduction consists of Abdel-Qaher’s definition of metonymy, with a criticism of the definition. The manuscript then focused on interpreting the poetic evidence in the Abd al-Qaher al-Jurjani chapter on metonymy, followed by a discussion. Moreover, the author then focused on other scholars’ take on metonymy. The conclusion of this manuscript summarizes the most important findings.